O-209 A quantitative solar ultraviolet radiation job-exposure matrix for the general working population of Europe (UVR EuroJEM). (14th March 2023) - Würtz, Else Toft; Pugdahl, Kirsten; Berglind, Ina A; ,; Cherrie, Mark PC; Dahlman-Höglund, Anna; Grandahl, Kasper; Macan, Jelena; Modenese, Alberto; Notø, Hilde; Solovieva, Svetlana; Straif, Kurt; et al.
Abstract : Introduction: Solar ultraviolet radiation (UVR) causes skin cancers, is a risk factor for cataract, and the primary predictor of serum vitamin D levels, but there are significant knowledge gaps in several health outcomes. Outdoor workers are exposed to high levels of solar UVR. The objective was to develop a European quantitative job-exposure matrix (JEM). This UVR JEM will be part of the EuroJEM for harmonised assessment of multiple exposure across Europe in EPHOR. Materials and Methods: A systematic literature search yielded 12 studies providing workday arithmetic mean erythema weighted UVR levels obtained by personal dosimeters (n=223) expressed by the Standard Erythemal Dose (SED) for 49 occupations classified by the European version of the International Standard Classification of Occupations, ISCO-88(COM). Nine experts (Northern, Central and Southern Europe) rated duration of outdoor work for all ISCO-88(COM) occupations that were included with season, duration of measurements and latitude as fixed effects in a mixed effects model. Study and occupation were included as random effects. The dependent variable was log-transformed SED harmonised (dosimeter type and location on the body) and weighted by the occupation exposure probability. Results: Modelled workday solar UVR level showed a monotonic increase with increasing expert rating. β-coefficients were 0.62 SED (95% CI -0.51:1.75) for 1 hour; 0.80 SED (95% CI -0.28:1.88) for 2–5 hours and 1.20 SED (95% CI 0.12:2.28) for >5 hours, compared to 0 hours. An eight-fold ratio between the highest and the lowest exposed occupations was seen. Our JEM estimates have highest exposure among farm-hands, concrete placers and related trades while waiters, wood-processing-plant operators, and several white collar occupations have the lowest exposure. Conclusion: This is the first general population quantitative JEM for occupational solar UVR exposure including personal measurements for investigation of exposure-response relations in epidemiological studies of health effects potentially associated with occupational UVR exposure.